The Improvement of the Reading Skill by Using Barron’s TOEIC Strategy for Vocational School - Umar Umar (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2017)
This research aims at finding out the use of Barron’s TOEIC strategy to improve the reading skill of the eleventh grade students at SMK Negeri Tinambung academic year 2010/2011.The objectives of the research were to find out whether or not the use of Barron’s TOEIC preparation course package significantly improves the reading ability of the eleventh grade students at SMK Negeri Tinambung academic year 2010/2011.The research used quasi experimental research design. The samples consisted of 50 students which belonged to two groups; experimental group and control group. The research data were collected using the reading test which was given to the both groups. The research results indicated that the use of Barron’s TOEIC strategy  did not significantly improve the reading ability of the eleventh grade students at SMK Negeri Tinambung academic year 2010/2011. The results of posttest of both groups were improved, but the use of Barron’s TOEICstrategy gave better progress than handbook of vocational school namely English in Progress Business & Management for SMK Year XI: TOEIC based Activities, By Munash F. Anwar. It was proved by the mean score of posttest of the experimental group was higher than the control group in reading (85.40 > 79.20).